6 - L’adoption des produits cosmétiques par les consommateurs camerounais : la forte incidence de la nouveauté perçue, de l’innovativité, de l’implication et des valeurs - Darius Djoma,; Victor Tsapi, (African Sociological Review, 2013)
The objective of this research is to identify and understand individual and perceptual variables, which could explain the decision process of purchasing a new product by the consumer, since these variables do not have the same behavior among different types of consumers. A confirma- tory survey conducted among 1,005 consumers of cosmetics in Cameroon, shows that the type of innovation (incremental or radical), perceived usefulness, and some individual variables (in- novativeness, involvement, and values) play a significant role in the adoption of new cosmetic product. recommendations are made to improve communication on new cosmetics products. Keywords: adoption of cosmetics, consumers, perception of novelty, methods of structural equa- tion modeling (SeM).